2016
DOI: 10.1007/s00520-016-3527-1
|View full text |Cite
|
Sign up to set email alerts
|

A prospective exploration of symptom burden clusters in women with breast cancer during chemotherapy treatment

Abstract: PurposeThe aim was to prospectively map symptom clusters in patients with stage I–IIIa breast cancer during standard chemotherapy treatment in a randomised study.MethodsParticipants completed the Memorial Symptom Assessment Scale (MSAS) at baseline, day 12 after the first and third cycle of FEC 75 or FEC 100, and day 12 after the last cycle of Taxotere. Cut-off values for symptom scores, a mean value based on each individual reporting a symptom including occurrence, frequency, severity and distress for inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 31 publications
4
57
1
1
Order By: Relevance
“…Finally, at least two of the following psychological symptoms, namely sadness, worry, anxiety and depression (the Psychological Cluster), were shown in eight studies to co‐occur in patients prior to receiving treatment 20,28,30,32–35,38 . Interestingly, (fatigue and/or sleep disturbance), were also shown to exhibit an association with some of the symptoms in this cluster, namely anxiety and depression, 30,33,34 suggesting that the symptoms in both clusters may mutually influence their occurrence.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Finally, at least two of the following psychological symptoms, namely sadness, worry, anxiety and depression (the Psychological Cluster), were shown in eight studies to co‐occur in patients prior to receiving treatment 20,28,30,32–35,38 . Interestingly, (fatigue and/or sleep disturbance), were also shown to exhibit an association with some of the symptoms in this cluster, namely anxiety and depression, 30,33,34 suggesting that the symptoms in both clusters may mutually influence their occurrence.…”
Section: Resultsmentioning
confidence: 98%
“…Of these 32 studies, 13 were cross‐sectional, 13–25 11 were longitudinal, 26–36 while the remaining eight involved a randomised clinical trial design 37–44 . Among these included studies, 16 involved the secondary analysis of the data of existing studies, 14,17,18,20,27,31,33–39,42–44 of which six were observational studies involving secondary analysis of data from randomised clinical trials 37–39,42–44 . Eleven of the included studies (34%) presented longitudinal changes in the composition of symptom clusters experienced by patients before, during and/or after cancer treatment 27,28,30,32–35,37–39,44 .…”
Section: Resultsmentioning
confidence: 99%
“…It is well documented that both the illness itself and the chemotherapy are accompanied by disturbing physical and psychological symptoms [ 7 , 8 ]. Experienced symptoms can vary due to types and combinations of chemotherapies, dosages, and length of treatments as well as individual factors such as age, comorbidity, lack of social support and coping strategies [ [9] , [10] , [11] ].…”
Section: Introductionmentioning
confidence: 99%
“…According to Miaskowski (2016), 'a priori' and 'de novo' are the two common approaches to conceptualise symptom clusters. 'A priori' studies of women with breast cancer identify different subgroups of women based on predetermined symptoms (Ho, Rohan, Parent, Tager, & McKinley, 2015;Sanford et al, 2014), whereas 'de novo' studies administer several symptom assessments and identified different clusters of symptoms that develop during the treatment course (Browall et al, 2017;Roiland & Heidrich, 2011). Most symptom cluster studies have evaluated symptom clusters during the short time treatment period (i.e.…”
Section: Introductionmentioning
confidence: 99%